Synthesis, thiol-yne "click" photopolymerization, and physical properties of networks derived from novel multifunctional alkynes - Chan, J.; Shin, J.; Hoyle, C.; Bowman, C.; Lowe, Andrew (American Chemical Society, 2010)
Multifunctional alkynes (2, 3, or 4 ynes per monomer) were prepared utilizing the nucleophile-catalyzed thio-Michael addition reaction from commercially available multifunctional thiols (2, 3, or 4 thiols) and propargyl acrylate. Real-time FTIR (RTIR) and NMR spectroscopies indicate that the conjugate addition under these conditions proceeds to high conversions within seconds using the nucleophilic catalyst dimethylphenylphosphine, in the absence of solvent, at ambient temperature, and with no side products. A family of polymer networks was prepared by the photoinitiated thiol-yne reaction employing a 2:1 ratio of thiol to alkyne, which resulted in uniformly cross-linked materials of systematically increasing cross-link density. Photopolymerization kinetic profiles indicate that the thiol-yne reaction proceeded rapidly to high conversion with conversions decreasing with increasing functionality of the thiol and/or alkyne groups. Differential scanning calorimetry (DSC) and dynamic mechanical thermal analysis (DMTA) results clearly indicate that the glass transition temperature increases as the overall cross-link density increases (from -10 to 42 °C by DMTA). An increase in the rubbery modulus (from 6 to 23 MPa at 70 °C) results as the functionality increases, with a concomitant decrease in the molecular weight between cross-links. © 2010 American Chemical Society.